When Does It Pay to be Good? Moderators and Mediators in the Corporate Sustainability–Corporate Financial Performance Relationship: A Critical Review - Grewatsch, Sylvia (Journal of business ethics, 2017)
In this paper, we review the literature on moderators and mediators in the corporate sustainability (CS)–corporate financial performance (CFP) relationship. We provide some clarity on what has been learned so far by taking a contingency perspective on this much-researched relationship. Overall, we find that this research has made some progress in the past. However, we also find this research stream to be characterized by three major shortcomings, namely low degree of novelty, missing investment in theory building, and a lack of research design and measurement options. To address these shortcomings, we suggest avenues for future research. Beyond that we also argue for a stronger emphasis on the strategic perspective of CS. In particular, we propose future research to take a step back and aim for an integration of the CS–CFP relationship into the strategic management literature.